Efficacy of Botanicals Against Mustard Aphid (Lipaphis Erysimi Kalt.) (Homoptera: Aphididae) On Brassica Campestris L. - Angala, Sofala; Alim, MD Abdul; Islam, MD Aminul; Zohora, Fatema Tuz (Bangladesh Journal of Botany, 2022)
Efficacy of neem leaf extract, mahogany seed dust, and neem seed kernel dust against the mustard aphid Lipaphis erysimi Kalt., (Homoptera: Aphididae) on the mustard plant (Brassica campestris L.) was investigated during November 2014 to January 2015. The trial included four treatments, namely T1: neem leaf extract, T2: mahogany seed dust, T3: neem seed kernel dust, T4: control. The treatments began 22 DAS and were repeated every 7 days. T4 had the maximum number (9500 ± 1226.3) of aphid pest population at 57 DAS, and the lowest number (3 ± 0.9) of aphid pest population was found in T4 at 29 DAS. The aphid population was found to be nil at 22 and 71 DAS in all treatments. Furthermore, in case of T2, the aphid population was zero at 29 DAS. There was no significant difference in aphid counts between the treatments, according to the ANOVA test. Only in T2, the aphid counts showed a significant difference by replicates. But the number of fruits and seed output of mustard were affected by the efficacy of botanicals against mustard aphid. T1 exhibited the highest percentage of fruits (27.7%), seeds (42.64%), and seed weight (54.9%). T1 had the highest proportion of healthy seed (75.91%), whereas T4 had the highest percentage of defective seed (45.49%). Aphid population is negatively correlated to average temperature and relative humidity in all treatments. Bangladesh J. Bot. 51(3): 615-623, 2022 (September)